The complex phenomenon of dysrational antibiotics prescribing decisions in German primary healthcare: a qualitative interview study using dual process theory - Poß-Doering, Regina; Kamradt, Martina; Stürmlinger, Anna; Glassen, Katharina; Kaufmann-Kolle, Petra; Andres, Edith; Wensing, Michel (Antimicrobial resistance and infection control, 2020)
Antibiotic prescription rates in primary care in Germany are moderate, but still considered too high. The ARena study (Sustainable reduction of antibiotic-induced antimicrobial resistance) was initiated to foster awareness and understanding of the growing challenge and promotes rational antibiotics use for acute, non-complicated and self-limiting infections.